Natural Disasters in Geography Education–Selected Results of Empirical Studies on the Students' Perspectives, Didactical Consequences, and Research Perspectives - Hemmer, Michael; Rahner, Maike; Schuler, Stephan (Journal of Geography Education, 2011)
The impact of students' conceptions and interests on organisation and effectivity of teaching is undisputable. The following article presents the results of different empirical studies dealing with natural disasters. In 2006, a study on students' interests was carried out in 6th grade of all school types. The central results – which have not been published so far – are presented on the basis of certain facets, contexts and operation methods of the topic natural disasters. Regarding the aspect "students' conceptions" the results of selected international studies are described. Here, emphasis is put on two studies from Taiwan and Florida, which consider the meta-level of Weltanschauung in student explanations of natural disasters, and thus differentiate between mythological and scientific approaches concerning students' conceptions. Didactical-methodological reflections and models on how to deal with natural disasters in geography lessons as well as perspectives on scientific education research complete this article.